2017
DOI: 10.3892/mco.2017.1197
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-ligand 1 expression is associated with fibrosarcomatous transformation of dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans (DFSP) is a locally invading tumor, characterized by the presence of the collagen type I α 1 (COL1A1)-platelet-derived growth factor (PDGF) β fusion gene. We herein report the case of a 31-year-old man with a history of resection of an abdominal wall DFSP. The patient presented with chest pain and a computed tomography scan revealed a large mass in the posterior mediastinum and another mass in the right lung. The mediastinal mass was a sarcomatous lesion expressing the COL1A1-PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Several different molecular genetic alterations have been proposed to account for this transformation, including genomic gains of COL1A1-PDGFB , losses of genomic material from 22q, mutations of TP53, activation of the PDGFR-β/Akt/mTOR pathway signaling, and microsatellite instability [ 22 ]. Most recently, single reports have suggested that over-expression of programmed cell death 1 ligand (PD-L1) [ 23 ] and fusion of MAP 3K7CL-ERG [ 24 ] may be implicated in the transformation of conventional DFSP to fibrosarcomatous DFSP. It’s worth noting that both the previously reported two cases of EMILIN2-PDGFD fusion DFSP exhibited a fibrosarcomatous histology and showed homozygous deletion of CDKN2A [ 9 ], which had also been identified in PGDFB -rearranged DFSPs and often observed in cases showing hypercellularity and fibrosarcomatous transformation morphology [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several different molecular genetic alterations have been proposed to account for this transformation, including genomic gains of COL1A1-PDGFB , losses of genomic material from 22q, mutations of TP53, activation of the PDGFR-β/Akt/mTOR pathway signaling, and microsatellite instability [ 22 ]. Most recently, single reports have suggested that over-expression of programmed cell death 1 ligand (PD-L1) [ 23 ] and fusion of MAP 3K7CL-ERG [ 24 ] may be implicated in the transformation of conventional DFSP to fibrosarcomatous DFSP. It’s worth noting that both the previously reported two cases of EMILIN2-PDGFD fusion DFSP exhibited a fibrosarcomatous histology and showed homozygous deletion of CDKN2A [ 9 ], which had also been identified in PGDFB -rearranged DFSPs and often observed in cases showing hypercellularity and fibrosarcomatous transformation morphology [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy was very limited but interestingly PD-L1 expression was detected in the metastasis but not in the primary tumor (a locally invading dermatofibrosarcoma). PD-L1 expression was probably induced by the fibrosarcomatous transformation of the initial tumor, contributing to the metastasis through escape from immune surveillance ( 79 ).…”
Section: Dna-alkylating Drugsmentioning
confidence: 99%
“…Loss of p16 expression was demonstrated in 2 of 12 classic DFSP and 2 of 6 FS-DFSP [ 119 ]. Programmed cell death 1 ligand (PD-L1) expression was detected in metastatic FS-DFSP, but not in the primary tumor, suggesting a role of PD-L1 in the metastasis of FS-DFSP [ 123 ]. Since PD-L1 expression in the tumor cells is involved in immune escape from T cell attack [ 124 ], PD-L1 signal pathway may be a potential target for metastatic FS-DFSP.…”
Section: Treatmentmentioning
confidence: 99%